Comparative Study of an Enhanced Oil Recovery process with various chemicals for Naharkatiya Oil Field - Hazarika, Kalpajit; Gogoi, Subrata Borgohain (International Journal of Applied Sciences and Biotechnology, 2014)
This paper reports the effect of using black liquor whose main constituent is Na- lignosulfonate, which is the effluent from Nagaon paper Mill, Jagiroad, Assam, along with Alkali and Co-surfactant in enhanced crude oil recovery from Upper Assam porous media. In this paper an attempt has been done to study the change in Inter Facial Tension (IFT) with different concentration of Surfactant and also a comparative study has been done determine the change in IFT with or without Alkali and Co-Surfactant. Increasing the surfactant concentration reduces the IFT, hence increases the recovery efficiency. Alkali changes the Wettability of reservoir rock and reduces the surfactant adsorption and also act as an in-situ surfactant production.DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11047 Int J Appl Sci Biotechnol, Vol. 2(4): 432-436